Obsessão securitária e educação cívico-militar: implicações na gestão escolar do Colégio Cívico Militar Professor Vicente de Carli - Marcis, Marileide (2025)
This dissertation is linked to line 2 of the Master's Program in Education at the State University of Western Paraná (UNIOESTE), Francisco Beltrão Campus. It portrayed the theme of the reality experienced by a school in Francisco Beltrão that adopted the civic-military conformation. Notably in terms of management (analyzed through institutional documents). The process of militarization of public schools in the state of Paraná is a recent educational policy, beginning in 2019 with the adhesion to the Civic-Military Schools Program (Pecim) of the federal government. This program expanded in 2020, after the approval of State Law No. 20,338/2020, which instituted the Civic Military Schools Program. According to this Law, the Paraná model presented guidelines and characteristics that were distinct from the Federal Government Program and from those of other Brazilian states, being structured mainly through a hybrid format, which provided for/provides for Technical Cooperation between the State Secretariat of Education and Sports and the State Secretariat of Public Security. As a result, school management was initially shared between a Military Director and the General Director (civilian). Since its approval, the Law has undergone significant changes, which have made it possible to make the criteria for selecting institutions more flexible and authorized the adhesion of a greater number of schools to the Program. The objective of this research was to understand how Shared Management has been carried out in a specific school that adopted the civic-military format in the city of Francisco Beltrão. To this end, we developed the following problematization: To analyze what knowledge has guided the school management of the Professor Vicente de Carli Civic-Military School, based on the insertion of influences from the field of militarization, since 2020. The research methodology initially adopted the case study. Subsequently, we adopted, more specifically, documentary analysis. The sources of analysis used were: official gazette, laws, resolutions, notices, normative instructions, bills, manuals of the Civic-Military Schools, Political Pedagogical Project, School regulations, which allowed us to understand how the management was thought and configured. Considering the scope and characteristics of this theme, the documents cited above were used as an analysis cutout, analyzed from the post-structuralist perspective. Contributing to these reflections were Garland (2001), Foucault (2014), the following documents: Pedagogical Political Project (PPP), Student Manual for Civic-Military Schools (CCM), and authors who specifically research shared management. The study allowed us to understand that shared management presents challenges to be overcome, such as the resistance of some students to the established rules. However, some of the main objectives, which are the reduction of violence, low school attendance, improvement in academic performance, increased discipline and greater awareness of civic values, providing the exercise of citizenship, seem to be under construction in the aforementioned school and, as we understand, should not be disregarded. However, these objectives, by themselves, are not enough to solve social and economic problems that are part of the students' families and that are reflected in the school's daily life.